Localized discoid lupus erythematosus in plaques. - Garofalo, L. (European Journal of Pediatric Dermatology, 2018)
The current patient has a form of lupus erythematosus that can be classified as localized discoid lupus erythematosus (LED) for the exclusive cutaneous involvement of the face and for the persistence of lesions in the same site (4). However, as in subacute LE there is neither atrophy nor follicular hyperkeratosis. LED is rare in the child (2); its incidence in a Pediatric Dermatology clinic is about 0.09% of all cases (1); 3% of cases occur in the first 15 years of life, less than 2% in the first 10 years of life (2). The relationships between LED and systemic lupus erythematosus have long been discussed (5): there are data that speak in favor of a single disease and data contrary to this thesis; it was especially discussed if LED could develop into systemic lupus erythematosus or not. According to some Authors (3) LED in children often turns into systemic lupus erythematosus, while other Authors (6) consider this transition to be exceptional. It is probable that these different opinions depend on the fact that in subjects with systemic lupus erythematosus there are sometimes findings that are reminiscent LED; on the contrary, it is exceptional that LED turns into a systemic lupus erythematosus.